2004
DOI: 10.1590/s1413-70542004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Inoculação de sementes de milho utilizando o Trichoderma harzianum como promotor de crescimento

Abstract: RESUMOConduziu-se este trabalho com o objetivo de estudar o efeito do fungo Trichoderma harzianum como promotor de crescimento de sementes de milho tratadas com diferentes fungicidas. O experimento foi realizado em vasos em casa-devegetação, adotando o delineamento experimental inteiramente casualizado em esquema fatorial (3x2), utilizando os tratamentos com fungicidas: Captan®, Maxim® e testemunha e inoculação (com e sem inóculo) em quatro repetições. As características agronômicas avaliadas foram: altura de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
5
13
0
11
Order By: Relevance
“…Na Tabela 2, observa-se que o crescimento (cm) de C. candelabrum, quando confrontado com os bioprotetores, foi inferior estatisticamente ao crescimento da testemunha, em que não houve confronto. Em estudo realizado por Martins-Córder e Melo (1998) (MELO, 1996) e plantas de milho (RESENDE et al, 2004). Respostas à aplicação de Trichoderma spp.…”
Section: Discussionunclassified
“…Na Tabela 2, observa-se que o crescimento (cm) de C. candelabrum, quando confrontado com os bioprotetores, foi inferior estatisticamente ao crescimento da testemunha, em que não houve confronto. Em estudo realizado por Martins-Córder e Melo (1998) (MELO, 1996) e plantas de milho (RESENDE et al, 2004). Respostas à aplicação de Trichoderma spp.…”
Section: Discussionunclassified
“…Since agriculture is a vital segment of local economies in the neotropics, most research in this region on Trichoderma has been directed to their biological control activities against phytopathogens. Studies have focused on biological control of plant pathogens with economical importance in cacao plantations, orchards, coffee, beans, cotton, flowers and rubber tree plantations, (Castro, 1996, Carsolio et al, 1994Hoyos-Carvajal et al, 2008;Rivas & Pavone, 2010;Samuels et al, 2000, to control the symbiotic fungus of the leaf-cutting ant Atta cephalotes (López & Orduz, 2003), as well as to study the ability of Trichoderma to improve plant vigour and stimulate crop growth (Bae et al, 2009, Hoyos-Carvajal et al, 2009b, Resende et al, 2004. Our knowledge of the distribution of Trichoderma species is constantly evolving in the context of current advances toward resolving the taxonomy of the genus.…”
Section: Diversity Of Trichoderma In Tropical Americamentioning
confidence: 99%
“…Further research has shown that seeds treated with Trichoderma have played an important role in increasing the biomass of plants such as papaya, tomato (Gravel et al, 2007;Tavares, 2009;Fontenelle et al, 2011), corn (Resende, 2004), eucalyptus (Fortes et al, 2007;Filho et al, 2008), chickpeas (Srivastava et al, 2008), beans (Hoyos-Carvajal et al, 2009) and rice (Almança, 2005).…”
Section: Resultsmentioning
confidence: 99%